2020
DOI: 10.1111/jfpp.14478
|View full text |Cite
|
Sign up to set email alerts
|

LC‐DAD‐ESI‐MS/MS characterization of elderberry flower ( Sambucus nigra ) phenolic compounds in ethanol, methanol, and aqueous extracts

Abstract: Wild plants have recently attracted attention due to their phenolic compounds and their potential positive effects on human health (Barros, Dueñas, Carvalho, Ferreira, & Santos-Buelga, 2012).Elderberry refers to several different varieties of the Sambucus tree, which is a flowering plant belonging to the Adoxaceae family. The most common type is Sambucus nigra, also known as the European elderberry, which has been used since ancient times. Elderberry flowers are distinguished by their intense, pleasant fragran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…6 The main phenolic acids in elderberry fruit were gallic acid (3.45 μg/100 g of dry weight) and gentisic acid (2.16 μg/100 g of dry weight), and the dominant flavonoids were rutin (813.08 μg/100 g of dry weight) and quercetin (228.83 μg/100 g of dry weight), 7 while the predominant phenolic acids in elderberry flower extracts were chlorogenic acid, 5-p-coumaroylquinic acid, and dicaffeoylquinic acid. 8 Rutin (3265.13 mg/kg of fresh flowers) and naringenin (734.15 mg/kg of fresh flowers) were found as the main flavonols and flavanones in elderberry flower extracts. 9 The richest anthocyanins in elderberry fruits were cyanidin 3-Osambubioside (344.48 mg/100 g of fresh weight) and cyanidin 3-O-glucoside (190.63 mg/100 g of fresh weight).…”
Section: ■ Bioactive Compounds In Elderberrymentioning
confidence: 95%
See 1 more Smart Citation
“…6 The main phenolic acids in elderberry fruit were gallic acid (3.45 μg/100 g of dry weight) and gentisic acid (2.16 μg/100 g of dry weight), and the dominant flavonoids were rutin (813.08 μg/100 g of dry weight) and quercetin (228.83 μg/100 g of dry weight), 7 while the predominant phenolic acids in elderberry flower extracts were chlorogenic acid, 5-p-coumaroylquinic acid, and dicaffeoylquinic acid. 8 Rutin (3265.13 mg/kg of fresh flowers) and naringenin (734.15 mg/kg of fresh flowers) were found as the main flavonols and flavanones in elderberry flower extracts. 9 The richest anthocyanins in elderberry fruits were cyanidin 3-Osambubioside (344.48 mg/100 g of fresh weight) and cyanidin 3-O-glucoside (190.63 mg/100 g of fresh weight).…”
Section: ■ Bioactive Compounds In Elderberrymentioning
confidence: 95%
“…It contains different (poly)­phenolic compounds, including phenolic acids, flavanones, flavonols, and anthocyanins, in its leaves and fruits . The main phenolic acids in elderberry fruit were gallic acid (3.45 μg/100 g of dry weight) and gentisic acid (2.16 μg/100 g of dry weight), and the dominant flavonoids were rutin (813.08 μg/100 g of dry weight) and quercetin (228.83 μg/100 g of dry weight), while the predominant phenolic acids in elderberry flower extracts were chlorogenic acid, 5- p -coumaroylquinic acid, and dicaffeoylquinic acid . Rutin (3265.13 mg/kg of fresh flowers) and naringenin (734.15 mg/kg of fresh flowers) were found as the main flavonols and flavanones in elderberry flower extracts .…”
Section: Bioactive Compounds In Elderberrymentioning
confidence: 99%
“…For example, Uzlasir et al 34 showed that solvent (water, 80% methanol, 80% ethanol), extraction temperature (80 and 100 °C) and extraction time (5 and 30 min) have an impact in the phenolic content of S. nigra flower extracts. They concluded that aqueous extracts were found to be rich in phenolic compounds and the highest phenolic content was determined in extracts obtained at 100 °C for 30 min (1360.9 ± 26.9 mg L −1 ), whereas the lowest was detected in the ethanol extracts (347.55–473.27 mg L −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…17 Other authors have also reported a similar phenolic profile of aqueous S. nigra flower extracts. 5,34…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation